Towards a Queer Futurity: New Trans Television - Ralph J. Poole (European Journal of American Studies)
While gay and lesbian characters have a steady presence in American television series by now, this is not the case with transgender persons. Although there is a significant number of shows with such characters, sometimes even in leading roles, this still is a marginal phenomenon. Casting debates, depictions of sexual violence and transphobic harassment, generational conflicts, non-normative sexuality, and family constellations are amongst the most pronounced issues to be discussed, when asking for a queer futurity that these series possibly envision. Have series such as Transparent, Orange Is the New Black, The L-Word, or Hit & Miss started to exploit such a potential? The paper aims at both an assessment of the status quo of transgender representations in current television series and at evaluating their respective aesthetic and political potential for a re-queering the American nation under the sign of transgenderism.